ASSESSMENT OF WEEVIL DAMAGE DEGREE OF BUCKWHEAT VARIETIES IN PRIMORSKY KRAI - A. V. Kuznetsova; A. G. Klykov (Зерновое хозяйство России, 2018)
The basic pest of buckwheat in Primorsky Krai is buckwheat weevil (Rhinoncus sibiricus Faust). The researches established that harmfulness of buckwheat weevil is seen during the whole period of vegetation and productivity loss is about 40% in average. The weevils make small round holes in the leaves, reducing assimilating surface of a leaf, and larvae damage the stem from the first to the fifth nod. It results in the curve of a stam, lodging and fracture. We carried out an assessment of weevil damage degree of buckwheat varieties in ecologic and competitive trials in Primorsky Krai. As a subject of the trials we took 37 varieties, 20 of which were de-veloped in Primorsky RIA, the rest ones were developed in All-Russian research Institute of Legumes and Groats, Tatarsky RIA, Bashkiriya RIA, Institute of Biologic Development after N.K. Koltsov. The carried out study showed that weevil damage degree of buckwheat varieties in ecologic and competitive trials was 42,5-89,3% in the period of germination and – 50,0-99,5% in the period of maturation. Weevil damage degree of leaves and stems didn’t depend on morphotype (indeterminate or determinate), color of flowers, ploidy level, period of vegetation, ecologic-geographical origin of the variety. We extracted a variety ‘Primorskaya 373’ of Primorsky RIA breeding and a determinate variety ‘Dizain’ of RIA of Legumes and Groats breeding, characterized by larvae damage of stem in the period of maturation on 60 and 50% respectively. The damage of a standard variety ‘Izumrud’, which is characterized with high productivity, was 75%.